Delegated authority and strengthening the role of regional governments in handling human trafficking crimes in Nunukan Regency - B, Jauchar; Jefri, Jefri; Hastira, Muh Fichriyadi; Mulka, Sry Reski; Fatimah, Andi Besse (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
Human trafficking in Indonesia's border regions is closely linked to illegal or non-procedural migration practices, particularly in Nunukan Regency, which borders Malaysia. This situation is exacerbated by a highly centralized governance structure, which limits the role of local governments in responding to the rapid and informal nature of migration and human trafficking. This study aims to analyse the policy framework for handling human trafficking crimes in the context of illegal migration, highlighting the limitations of local government authority in a decentralized system. This study uses a literature review and qualitative policy analysis based on documents, including laws and regulations, national and regional policies, relevant academic literature, and reports from international organizations. The analysis was conducted using a transnational governance framework and the concept of delegated authority. The results of the analysis show that there is a governance gap in the supervision of non-procedural migration, data collection on migrant workers, cross-border coordination, and initial protection of victims of human trafficking due to the dominance of central government authority. These findings are analytical and normative, not empirical, and show that the limitations of local governments' roles are a consequence of the policy's institutional design. This study concludes that the development of a limited, accountable delegated authority scheme has the potential to strengthen local governments' roles in border areas in addressing the link between illegal migration and human trafficking, and recommends further empirical research to test its effectiveness in implementation.